2002
DOI: 10.1161/01.cir.0000015077.12680.2e
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Reentrant Circuits in Left Atrial Macroreentrant Tachycardia

Abstract: Background-Left atrial macroreentrant tachycardia (LAMRT) has not been characterized in detail.Methods and Results-Twenty-eight patients with LAMRT, including 4 patients with ablated typical atrial flutter (AFL), underwent electroanatomic mapping of the left atrium (LA) between February 1999 and October 2001. LA maps were performed during LAMRT in 26 patients and during sinus rhythm in 2 patients. Electrically silent areas or continuous lines of double potentials were identified as acquired anatomic barriers i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 198 publications
(51 citation statements)
references
References 17 publications
3
48
0
Order By: Relevance
“…In our early experience using segmental PV isolation, the most common type of AT was a focal pattern originating from a segment of a previously isolated PV. 18 These findings are in agreement with the findings of Ouyang and colleagues 19 who found that more of 80% of left ATs had focal origin from the PV. In contrast, when linear ablation is performed in addition to PVI, the majority of AT are macroreentrant.…”
Section: Early Versus Late Recurrencesupporting
confidence: 90%
See 1 more Smart Citation
“…In our early experience using segmental PV isolation, the most common type of AT was a focal pattern originating from a segment of a previously isolated PV. 18 These findings are in agreement with the findings of Ouyang and colleagues 19 who found that more of 80% of left ATs had focal origin from the PV. In contrast, when linear ablation is performed in addition to PVI, the majority of AT are macroreentrant.…”
Section: Early Versus Late Recurrencesupporting
confidence: 90%
“…19 Therefore, we examine all previously created lines for reconnected segments and look for low amplitude, fragmented or double potentials that represent slow conduction. In our experience and others, the reentry circuit with a protected isthmus can be identified in …”
Section: Electrophysiologic Study -Diagnostic Maneuversmentioning
confidence: 99%
“…9,11 Mapping was performed with a 3.5-mm-tip catheter (ThermoCool Navi-Star, Biosense-Webster) during coronary sinus pacing or sinus rhythm. In case of AF, sinus rhythm was restored by external cardioversion.…”
Section: D Electroanatomic Mapping and Irrigated Radiofrequency Ablamentioning
confidence: 99%
“…Successful ablation of macroreentrant AT with few RF applications in most patients indicates that the gaps responsible for AT were small and the critical isthmus was narrow, as recently reported. 16 Applications of RF energy on the earliest activation site also eliminated focal AT in most patients without complication.…”
Section: Catheter Ablation Results In Patients With Postablation Atmentioning
confidence: 97%